Modelling debt financing behaviour of Malaysia SMEs - Haron, Razali (IEEE, 2015)
This study models the debt financing behaviour of SMEs (Enterprise 50) in Malaysia to determine the existence of target debt, speed of adjustment and rational financing by utilizing panel data from 2009-2013. The estimated debt financing model revealed certain factors such as profitability, tangibility,business risk, growth, size, liquidity and share price performance significantly influence target debt financing. The study found that 52% of the SMEs examined adjust their financing rationally. Further investigation revealed that under-levered SMEs adjust relatively faster to be at target debt relative to the over-levered counterparts. SMEs that are practicing rational financing behaviour would either reduce or increase their debt intake to reach to their target debt level. This study contributes to the literature and fills the gap by enhancing the understanding of debt financing of SMEs in Malaysia.